Monocyte-bound monoclonal antibodies inhibit the Fc gamma RI-mediated phagocytosis of sensitized red cells: the efficiency and mechanism of inhibition are determined by the nature of the antigen. - Shepard, S L (1997)
Monocyte-binding monoclonal antibodies (mAbs) inhibited the Fc gamma receptor I (Fc gamma RI)-mediated phagocytosis of red cells sensitized with human monoclonal immunoglobulin G (IgG) anti-D (E-IgG) via three distinct mechanisms depending on their specificity. First, all monocyte-binding mAbs tested inhibited the adherence (and hence the phagocytosis) of E-IgG. They also inhibited the binding of fluorescein isothiocyanate (FITC) conjugated IgG anti-D. This inhibition of ligand binding was more efficiently promoted by murine (m) IgG2a than mIgG1 mAbs and presumably involved receptor blockade via the formation of antigen (Ag)-mAb-Fc gamma RI complexes on the monocyte membrane. Monocytes passively sensitized with human monoclonal anti-D (M-IgG) were used in experiments to distinguish between inhibition of ligand binding and inhibition of phagocytosis. In this way, it was shown that mAbs to transmembrane molecules (CD11b/CD18, CD44, and HLA) inhibited the phagocytosis of red cells adherent to M-IgG. Under the same conditions, mAbs to glycosylphosphatidylinositol (GPI) linked molecules (CD14, CD55 and CD59) did not inhibit phagocytosis. These data suggested a second mechanism of inhibition of Fc gamma RI-mediated phagocytosis that involved the cross-linking of a proportion of Fc gamma RI (i.e. those not ligated with IgG anti-D) to molecules which are relatively constrained in the cell membrane. A third mechanism of inhibition was revealed by the use of F(ab')2 fragments of mAb to CD11b which inhibited Fc gamma RI-mediated interactions with E-IgG in a manner that did not involve IgG (Fc) crosslinking or blockade of Fc gamma RI. In this respect, Fc gamma RI-mediated phagocytosis was more susceptible to inhibition than receptor-mediated adherence.